The Existence and Consistency of Halal Certificates in the Global Ecosystem of Halal Products and Services - Hidayat, Yusup; Machmud, Aris (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2024)
Halal certification is an absolute requirement for the eligibility of goods and services for Muslims, however, halal is not just a piece of paper or a halal logo, but more to the substance of the process and quality of halal guarantees. The research objective is to examine the position of the Ministry of religion in guaranteeing the halal-ness of products and services. The author uses a normative juridical research form with a statutory regulatory approach related to halal product guarantees. The author concludes that cooperation and synergy between institutions under the Ministry of Religion including the Halal Product Guarantee Agency (LPH) and MUI and the supervisory agency (BPOM) are crucial in ensuring the halal supply chain of products and services to maintain the halal ecosystem both formally and substantially. The author thinks that in regulations related to halal product guarantees, there are inconsistencies and also the occurrence of ambiguity in norms which has the potential to create legal uncertainty as stated in articles 171 and 172 of Government Regulation Number 39 of 2021 which are contradictory in content where article 171 states that Government Regulation Number 30 of 2019 can still apply as long as it does not conflict with the law on halal product guarantees, while Article 172 states that the previous PP is repealed and no longer valid.